Analisis Teori Belajar Konstruktivisme dalam pembelajaran Teknik Informatika Di SMAN 8 Luwu Timur - Muhaimin Burhanuddin; Farida Febriati (STKIP Subang, 2026)
Learning at the high school level is certainly inseparable from the relationship between learning theories taught by a teacher to students, teachers are also tasked with instilling learning in accordance with the basic values ​​​​agreed upon by the Indonesian nation. Learning contained in the concept of constructivist learning theory is a learning model that emphasizes students' current activities, as stated by Jean Piaget, he explained that the learning process begins with cognitive conflict activities, so that at the end of the learning process students will build their own knowledge through interaction with the environment. Constructivist learning theory was also put forward by Vygotsky, he explained that the constructivist learning process is based on social interaction / requires the help of others (schafollding). The purpose of writing this article is to describe the theory of constructivism implemented by teachers in informatics learning, especially at the high school level. This study uses qualitative descriptive research, the instruments used are observation sheets and interview guidelines. The subjects in this study were informatics teachers of class X.B SMAN 8 Luwu Timur. The results of this study indicate that teachers have carried out the learning process effectively, namely by actively interacting with students in the learning process. The application of this theory is demonstrated by the emergence of all stages of constructivism theory, such as apperception, exploration, discussion and concept explanation, and concept development and application. Ultimately, students are able to construct their own knowledge effectively.